Daily living activities of the elderly in nursing homes - Fathi, M; Yaghmaei, F; Shahsavari, S (Advances in Nursing & Midwifery, 2009)
Background: Aging is inevitable, starts gradually as the last stage of development in all people leading to alterations in body compounds and decreased efficiency of organs and affects on physical ability at different levels. Deterioration of physical abilities and its resultant limitations reduces the independence of the elderly and increases their reliance on others. WHO reports suggest that inactivity or immobility in living is a leading cause of morbidity and mortality worldwide. Purpose: This descriptive study was conducted to assess physical activities of the elderly and identify their problems and needs in nursing homes of Sanandaj. A healthcare plan was then developed according to their needs. Methods 88 elders (over 65) from 2 governmental and private nursing homes took part in the study. A questionnaire (Independence in Daily Living Activities) developed in 2006 with 20 items describing all daily physical activities was used for data collection. It was completed by observation and interview. It divides independence into 2 levels and a 5-point Likert scale (from 0 to 4 points) including absolutely independent, relatively independent, relatively dependent, absolutely dependent, and inactive because of nonphysical problems is used for scoring. The scores range between 20 and 80 or less. Results 51% of the elderly was male, 56% between 65 and 75, 88% illiterate, 61% from other towns and 42% resided at nursing homes less than 3 years. 6 (6.82%), 51 (57.95%), 26 (29.55%) and 5 (5.68%) elders were absolutely independent, relatively independent, relatively dependent and absolutely dependent respectively. The last group needed constant care for all of their daily activities. Conclusion Being in nursing homes requires daily activities and some tasks for self-care. Activities of the elderly for mobility and self-dependence help maintain their health but inactivity can increase their need to carers and assisting or ambulatory devices. The importance of activity limitations is revealed when their physical mobility is assessed by an appropriate tool to provide a criterion for predicting as well as planning healthcare services and, finally, for their self-care and health promotion. The tool applied in this study is recommended. Keywords: Activities of daily living, Elderly, Nursing homes.